Social identity motivations and intergroup media attractiveness. (January 2020) - Joyce, Nick; Harwood, Jake
In this experiment we manipulated three features (intergroup social comparison, outgroup character stereotypicality, intergroup intimacy) of an intergroup TV pilot proposal. We examined how two underlying social identity motivations (social enhancement, social uncertainty reduction) were gratified by the aforementioned features, and whether this gratification predicted media attractiveness. Findings indicate that when social comparison was manipulated to advantage the ingroup, intergroup media gratified existing social enhancement motivations and led to audiences rating the show as more entertaining and attractive. This finding was most clearly evident in the absence of intergroup romance. The gratification of social uncertainty reduction motivations was also shown to increase audience perceptions of intergroup media attractiveness, but outgroup stereotypicality was weakly associated with the gratification of this motivation. These results are discussed in terms of both theoretical implications as well as applications to media campaigns.